Waste management in European law : the example of Napels and Campania - Panoussis, Ioannis K.; Post, H. H. G. (Eleven International Publishing, 2014)
A few years ago, almost daily television reports on the 'waste crisis' in the Campania, the region of Naples, showed vividly that waste management can become a rather nightmarish undertaking. Is this an Italian speciality or is it also more in general a complex and difficult subject? For many years, waste management has been an activity regulated by European law. This book analyzes the salient features of the relevant law by critically assessing the relevant instruments and the jurisprudence of both the European Court of Justice and the European Court of Human Rights. The Neapolitan waste cris.